Acupuncture for migraine: A systematic review and meta-regression of randomized controlled trials - Chunyan Yang; Min Wu; Qin Luo; Guixing Xu; Liuyang Huang; Hao Tian; Mingsheng Sun; Fanrong Liang (Complementary Therapies in Medicine, 2024)
Objectives: This meta-analysis aimed to explore the relationship between the dose of acupuncture sessions, acupuncture frequency, and acupuncture duration and its effects on migraine. Methods: Eight databases were searched for randomized controlled trials (RCTs) evaluating the efficacy of penetrating manual acupuncture for migraine published in English and Chinese from inception to June 20, 2024. The robust-error meta-regression (REMR) approach and non-linear meta-regression with restricted cubic spline (RCS) were used to investigate the dose-response association between acupuncture sessions, acupuncture frequency, and acupuncture duration and the frequency of migraine attacks. The potential nonlinear relationships was tested by restricting the regression coefficient to zero and a P value＜0.1. The statistical analysis was conducted using Stata 17.0. The risk of bias was independently assessed by two reviewers using the Cochrane tool. The reporting quality for acupuncture procedures was evaluated by STRICTA criteria. Results: Thirty-two RCTs involving 1562 participants were included, and the results showed a J-shaped dose-response association between acupuncture sessions, acupuncture frequency, and acupuncture duration and migraine attack frequency. After 16 acupuncture sessions, the change in the frequency of migraine attacks was 3.95 (95 %CI: 3.13 to 4.77). Three sessions of acupuncture a week resulted in a significant decrease in the frequency of migraine attacks, reaching 4.04 (95 % CI: 2.49 to 5.58). After two months of acupuncture, the frequency of migraine attacks decreased significantly, showing a difference of 4.05 (95 % CI: 3.61 to 4.49). Subsequently, the improvement trend gradually flattened, yielding diminishing benefits to patients. The risk of bias showed that seven studies were rated as “low risk”, two were rated as “high risk”, and the others were rated as “unclear risk”. The reporting quality of RCTs of acupuncture for migraine remain suboptimal. Conclusions: A non-linear dose-response relationship was found between acupuncture sessions, acupuncture frequency, and acupuncture duration and migraine attack frequency. The results of our study recommend 16 sessions of acupuncture with a frequency of 3 sessions/week and a treatment duration of 1.5 to 2 months. Registration number: This meta-analysis has been registered on PROSPERO (CRD42023400493).